Machinability, weldability and surface treatment studies of SDSS 2507 material-A review. (2021) - George, Pradeep; Leo Dev Wins, K.; Ebenezer Jacob Dhas, D.S.; George, Pramod; B, Anuja Beatrice
Abstract: Super duplex stainless steel 2507, is a difficult to machine material due to high chromium content. Knowledge on machinability, weldability and surface treatment of 2507 super duplex stainless steel material is necessary due to the increase in demand of this material in variety of application in engineering and medical fields. In this review, machinability studies on turning and milling of SDSS 2507 is discussed. Weldability of SDSS 2507 material is also reviewed in this paper. Effect of heat and chemical treatments on strength, ductility, resistance to corrosion, wear, crack propagation and pitting characteristics of this material are included. Machining with wet, minimal quantity lubrication and dry conditions are analyzed. From the review, it was found that machinability can be improved by machining at high cutting speed and low feed rate along with proper selection of tool. Welding of SDSS 2507 material with similar and dissimilar materials is also discussed. Literatures on the studies on machining of SDSS 2507 material, especially on milling of SDSS material is very less compared to turning operation. Review revealed that SDSS 2507 material possess better strength, ductility and corrosion resistance properties compared to Austenitic SS and Ferritic SS. The present paper recommends the usage of tougher insert grades for machining. From this review, it is clear that SDSS 2507 material can be used in corrosion prone environments due to its high resistance to corrosion and pitting characteristics. SDSS 2507 material can also replace duplex stainless steel in storage and transportation of petroleum products, piping, etc. due to its exceptional characteristics.